Depression after Stroke and Risk of Mortality: A Systematic Review and Meta-Analysis - Francesco Bartoli; Nicoletta Lillia; Annamaria Lax; Cristina Crocamo; Vittorio Mantero; Giuseppe Carrà; Elio Agostoni; Massimo Clerici (Stroke Research and Treatment)
Background. Depression after stroke may have great burden on the likelihood of functional recovery and long-term outcomes. Objective. To estimate the association between depression after stroke and subsequent mortality. Methods. A systematic search of articles using PubMed and Web of Science databases was performed. Odds ratios (ORs) and hazard ratios (HRs) were used as association measures for pooled analyses, based on random-effects models. Results. Thirteen studies, involving 59,598 subjects suffering from stroke (6,052 with and 53,546 without depression), had data suitable for meta-analysis. The pooled OR for mortality at followup in people suffering from depression after stroke was 1.22 (1.02–1.47). Subgroups analyses highlighted that only studies with medium-term followup (2–5 years) showed a statistically significant association between depression and risk of death. Four studies had data suitable for further analysis of pooled HR. The meta-analysis revealed a HR for mortality of 1.52 (1.02–2.26) among people with depression after stroke. Conclusions. Despite some limitations, this paper confirms the potential role of depression on post stroke mortality. The relationship between depression and mortality after stroke seems to be related to the followup duration. Further research is needed to clarify the nature of the association between depression after stroke and mortality.